Stanisław Przybyszewski — mizogin czy poszukiwacz miłości idealnej? - Murzicz, Ewelina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
This article presents and analyses the motif of women in Stanisław Przybyszewski‘s novels. The author focused on the woman‘s nature and presented the way it influenced the man‘s character and life. Przbyszewski‘s work is an attempt at answering questions about the point of love and desire; it also includes problems connected with metaphysical side of love and impossibility to achieve any unity between the man and the woman.